Temporal pole abnormalities in temporal lobe epilepsy with hippocampal sclerosis: Clinical significance and seizure outcome after surgery. (November 2015) - Di Gennaro, Giancarlo; D'Aniello, Alfredo; De Risi, Marco; Grillea, Giovanni; Quarato, Pier Paolo; Mascia, Addolorata; Grammaldo, Liliana G.; Casciato, Sara; Morace, Roberta; Esposito, Vincenzo; Picardi, Angelo
Highlights: Temporopolar abnormalities are common MRI findings in temporal lobe epilepsy (TLE) due to hippocampal sclerosis (HS). The presence of temporopolar abnormalities did not influence seizure outcome in patients who had TL resection for HS. Temporopolar abnormalities might be regarded as a marker of epilepsy chronicity in TLE–HS. Abstract: Purpose: To assess the clinical significance of temporal pole abnormalities (temporopolar blurring, TB, and temporopolar atrophy, TA) in patients with temporal lobe epilepsy (TLE) and hippocampal sclerosis (HS) with a long post-surgical follow-up. Methods: We studied 60 consecutive patients with TLE–HS and 1.5 preoperative MRI scans who underwent surgery and were followed up for at least 5 years (mean follow-up 7.3 years). Based on findings of pre-surgical MRI, patients were classified according to the presence of TB or TA. Groups were compared on demographic, clinical, neuropsychological data, and seizure outcome. Results: TB was found in 37 (62%) patients, while TA was found in 35 (58%) patients, always ipsilateral to HS, with a high degree of overlap (83%) between TB and TA ( p < 0.001). Patients with TB did not differ from those without TB with regard to history of febrile convulsions, GTCSs, age of epilepsy onset, side of surgery, seizure frequency, seizure outcome, and neuropsychological outcome. On the other hand, they were significantly older, had a longer duration of epilepsy, and displayed lower preoperative scores on several neuropsychological tests. Similar findings were observed for TA. Multivariate analysis corroborated the association between temporopolar abnormalities and age at onset, age at surgery (for TB only), and lower preoperative scores on some neuropsychological tests. Conclusions: Temporopolar abnormalities are frequent in patients with TLE–HS. Our data support the hypothesis that TB and TA are caused by seizure-related damages. These abnormalities did not influence seizure outcome, even after a long-term post-surgical follow-up.